Analysing the moderating effects of generational cohorts on brand loyalty in the Malaysian footwear industry - Lai, Ruixia; Teo, Siew Chein (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study aims to determine if the factors affecting brand loyalty in the footwear industry are moderated by generational cohorts (Baby Boomers, Generation X, and Millennials). It also examines if product quality, product style, produce price, brand image, service quality, and store environment are antecedents to brand loyalty in the Malaysian footwear industry. Insights into brand loyalty in Malaysia’s footwear industry would help domestic brands gain customer loyalty and allow penetration into the global footwear market. Web-based, selfadministrated survey questionnaires were distributed to 200 respondents. Several statistical analyses were performed using SPSS 22 software. The results indicate that four of the predetermined antecedents, product quality, product style, brand image, and store environment significantly influence brand loyalty in the Malaysian footwear industry. Malaysian footwear consumers from different age groups (generational cohorts) also revealed different purchasing patterns and buying behaviour.